INTELLECTUAL POTENTIAL OF THE ENTERPRISE ACTIVATING AND INTELLECTUAL PROPERTY PROCESSES IN THE INTENSIFICATION OF KNOWLEDGE-BASED ECONOMY - Ostrovska, Halyna (Social Economics, 2020)
The article is devoted to the issue of activating the intellectual potential of the enterprise and intensification of intellectual property processes in a knowledge-based economy. Foreign experience in the field of scaling the intellectual property market was studied, the state and tendencies of its development were covered. Challenges for Ukraine in the context of commercialization of intellectual property rights are substantiated. The sphere of intellectual property as the main tool of scientific-technological important transformation directions and creative development in general are singled out. The institutional regulation of intellectual potential and commercialization of the intellectual activity in a knowledge-based economy results processes effective use is highlighted. Based on the study of legal, financial and organizational institutions that stimulate the development of intellectual and innovative technologies, the knowledge-based economy key trends are summarized in the context of intellectual property based on institutional approach capitalization paradigm: accelerating the intellectual resources transformation into intellectual capital; correspondence of the remuneration received by the specialist to payment of knowledge; merging intellectual capital with financial. It is proved that the influence of institutions in the Ukrainian economy leads to a disproportion between the intellectual resources formation spheres and intellectual capital; the intellectual capital use by institutional conditions processes slowing down. The main directions of intellectual property sphere development in connection with the process of knowledge-based economy innovative development are offered. A set of measures has been developed for further development of intellectual potential and intellectual property market scaling in Ukraine, which will provide comparable in quality or superior to world best practices conditions for intellectual creativity.